Examining People’s Experiences of Working in Collaborative Relationships While Conducting Inclusive Research Involving Persons with Intellectual Disabilities - Kim van den Bogaard; Noud Frielink; Alice Schippers; Petri Embregts (Social Sciences, 2024)
This study examined the experiences of working in collaborative relationships while conducting inclusive research involving persons with intellectual disabilities. More specifically, the study explored work relationships, social relationships, and factors that influence collaboration within inclusive research teams. Interviews were conducted with nine researchers with intellectual disabilities, eight academic researchers, and nine principal investigators who were all involved in six inclusive research projects together. The analysis of the interviews produced four themes: (1) the diverse nature of the involvement of researchers with intellectual disabilities; (2) the significance of involving researchers with intellectual disabilities within academic research; (3) shaping equity in research projects; and (4) stereotyping hindering collaborations with researchers with intellectual disabilities. These findings have implications for research and practice, both in terms of promoting inclusive research and facilitating the meaningful participation of persons with intellectual disabilities within various aspects of society, including education, employment, healthcare, and social activities.